[Laiškas] / Jankovskis (Jankowski) Placidas (John of Dycapl), rašytojas, vertėjas - J. K. Vilčinskiui. - (:unkn) unknown (My University, 1858)
1 laiškas apie karikatūristo A. Bartelso eskizų išspausdinimą Vilniuje.
Keywords: Laiškai; Autografų kolekcija; Jankowski, Płacyd, 1810-1872; Vilčinskis, Jonas Kazimieras, 1806-1885; Bartels, Artur, 1818-1885; Vilnius (Lietuva)